Sebaceous Carcinoma of the Penis: A Rare, Dangerous Clinical Entity and the Importance of Immunohistochemistry in Diagnosis - Vikram Sahni; David S. Cassarino (Case Reports in Dermatological Medicine)
We report a very rare case of pathologically confirmed sebaceous carcinoma of the glans penis with multiple areas of lymphovascular and perineural invasion and multiple lymph node metastases. The importance of immunohistochemical staining in diagnosis is also reviewed.